Effects of monoamine manipulations on the personality and gene expression of three-spined sticklebacks - Abbey-Lee, Robin N. (Linköping University, 2019)
Among-individual behavioral differences (i.e. animal personality) are commonly observed across taxa, although the underlying, causal mechanisms of such differences are poorly understood. Animal personality has been implicated in correlations with physiological functions as well as affecting fitness-related traits. Variation in many aspects of monoamine systems, such as metabolite levels and gene polymorphisms, has been linked to behavioral variation. Therefore, here we investigated the potential role of monoamines in explaining individual variation in personality, using two common pharmaceuticals that respectively alter the levels of serotonin and dopamine in the brain: fluoxetine and ropinirole. We exposed three- spined sticklebacks, a species that shows animal personality, to either chemical alone or to a combination of the two chemicals, for 18 days. During the experiment, fish were assayed at four time points for the following personality traits: exploration, boldness, aggression and sociability. To quantify brain gene expression on short- and longer-term scales, fish were sampled at two time points. Our results show that monoamine manipulations influence fish behavior. Specifically, fish exposed to either fluoxetine or ropinirole were significantly bolder, and fish exposed to the two chemicals together tended to be bolder than control fish. Our monoamine manipulations did not alter the gene expression of monoamine or stress-associated neurotransmitter genes, but control, untreated fish showed covariation between gene expression and behavior. Specifically, exploration and boldness were predicted by genes in the dopaminergic, serotonergic and stress pathways, and sociability was predicted by genes in the dopaminergic and stress pathways. These results add further support to the links between monoaminergic systems and personality, and show that exposure to monoamines can causally alter animal personality.

Raw data used for analyses in published manuscript: Robin N. Abbey-Lee, Anastasia Kreshchenko, Xavier Fernandez Sala, Irina Petkova and Hanne Løvlie. 2019 Effects of monoamine manipulations on the personality and gene expression of three-spined sticklebacks. Journal of Experimental Biology 222, jeb211888. doi:10.1242/jeb.211888


The dataset was originally published in DiVA and moved to SND in 2024.
Effects of monoamine manipulations on the personality and gene expression of three-spined sticklebacks
Keywords: animal behavior; animal behavior; fish; fish; serotonin; serotonin; ecotoxicology; ecotoxicology; dopamine; dopamine; cocktail effects; cocktail effects; Behavioural Sciences Biology; Etologi